Lipoprotein(a), cardiovascular events, and benefit of P2Y12 inhibition: insights from the PEGASUS-TIMI 54 trial. (3rd October 2022) - Patel, S; Morrow, D; Bonaca, M; Palazzolo, M; Jarolim, P; Steg, P G; Bhatt, D; Storey, R; Cohen, M; Braunwald, E; Sabatine, M; O'Donoghue, M
Abstract: Background: Lp(a) plays a causal role in atherogenesis and may exert pro-thrombotic effects by inhibiting fibrinolysis owing to its structural homology with plasminogen. Patients with higher Lp(a) concentrations may derive greater benefit from anti-thrombotic therapy. Purpose: We assessed whether patients with higher Lp(a) derive greater risk reduction from P2Y12 inhibition with ticagrelor vs. placebo on a background of aspirin therapy. Methods: Lp(a) concentration was measured (Randox) in a prospective nested cohort of 8, 967 pts enrolled in PEGASUS-TIMI 54, a randomized trial of ticagrelor vs. placebo in patients 1–3 years post MI (median follow-up: 2.7 y). Lp(a) was dichotomized at 200 nmol/L as an established threshold of risk. The prespecified MACE endpoint was CV death, MI or stroke, with KM rates reported at 3y. Cox proportional hazards were used to assess the relationship between Lp(a), MACE and treatment benefit. Models were adjusted for relevant baseline characteristics including apolipoprotein B. Results: The median Lp(a) was 29 (25th-75th percentile: 12–137) nmol/L. A total of 1, 053 pts (11.7%) had a high Lp(a) (≥200 nmol/L). In the pooled trial population, high Lp(a) concentration was associated with a 29% higher risk of MACE (9.1% vs 7.6%; adjusted hazard ratio [adj HR] 1.29, 95% confidence interval [CI] 1.02–1.62; p=0.03), including a 37% higher risk of MI (6.9% vs. 5.3%; adj HR 1.37, 95% CI 1.05–1.79; p=0.02). The hazard ratios for MACE with ticagrelor vs. placebo were 0.73 (95% CI 0.48–1.11) for patients with higher Lp(a) and 0.88 (95% CI 0.74–1.05) for patients with lower Lp(a) (p-interaction=0.41; Figure 1). The absolute risk reductions were 2.4% and 1.2%, respectively. Conclusion: Lp(a) above 200 nmol/L identifies patients with prior MI at increased risk of MACE who may derive greater absolute risk reduction from treatment with ticagrelor. These exploratory observations provide insights for therapeutics that are evaluating the clinical benefit of Lp(a) reduction. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The PEGASUS-TIMI 54 trial was funded by AstraZeneca